Keterkaitan Bobot Pekerjaan dan Situasi Kerja dengan Kedisiplinan Kerja Perawat - Huda, Taufik; Perceka, Andhika Lungguh; Rifki, Muhammad; Erlinawati, N. Ai; Rusyani, Herlin (Jurnal Ners, 2024)
The successful implementation of the work of the health center when carrying out its role is indicated by the best quality of service. Excellent service, friendliness and timeliness of treatment provided to patients are closely related to nurses' work discipline. The instability of work weight is another manifestation of the beginning of fatigue, boredom and stress due to work, to the point that it affects the work discipline of nurses. Work discipline is a component that affects the work situation among several other components. This research has a direction In 2021, The goal was to evaluate how the workload and work environment relate to the level of work discipline among nurses at the Haurpanggung Health Center Garut. This study employs a descriptive correlation design, with a sample of 42 nurses. The findings of this research indicate that the majority of nurses view their workload as substantial or burdensome, most of them find the work environment unfavorable, and a significant number of nurses at the Health Center lack discipline. The inference made is that there exists a relationship between the workload and the discipline of nurses, as well as a connection between the work environment and nurse discipline specifically within the Haurpanggung Garut.